OUTPLACEMENT MODEL FOR EMPLOYEES CAREER DEVELOPMENT PROMOTION - Rokjane, Baiba; Dislere, Vija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This article addresses the problem of providing career guidance to professionals who are expected to be made redundant. The aim of this thesis is to develop and to do expert-evaluation of the Outplacement Model for Employees Career Promotion (hereinafter referred to as “Model”). The study was developed in the Latvia University of Agriculture, the Institute of Education and Home Economics within the Master study programme Career Counsellor. An expert evaluation of the Model was carried out with the participation of 5 experts in the field of career counselling and personnel management. In general, expert assessments of the overall Model rating (7-9 points) are close to the maximum possible rating (10 points). The provision of Outplacement services in Latvia has a wide range of benefits to the employee, employer and society as a whole. The developed Model will help employees to become more aware of their abilities and return to the labour market soon, after leaving their previous job. The Model can be used by career guidance providers for organizations and employers, career counsellors, and companies providing outplacement services.